Documentation On Medicinal Plants of Deva Deva Vana Botanical Garden of Bidar District, Karnataka (International Journal of Scientific Research in Science and Technology, 2024)
The present study was undertaken to document medicinal plants of Deva Deva vana Botanical garden of Bidar district, karnataka. Deva Deva vana literally means ‘Forest of divine/celestial beings’ A Botanical garden maintained by the Forest department around 6 km from Bidar – Hyderabad Highway. It is home to around 200 medicinal plants and trees, and considered sacred. It is divided into around 10 gardens and a nursery which is classified according to a particular theme like Nandana vana, Ashoka vana, Navagraha vana, Rock Garden, shiva panchayath vana, Phala pushpa vana,..etc the documentation of medicinal plants helps to recognize the overall ecological conditions, conservation and gives profound understanding of the economic medicinal and traditional importance of medicinal plants diversity. The present research documentation work was started in February 2023 and completed in June 2024. The present study reported that 147 Medicinal plant species belongs to 64 families distributed and conserved in Deva Deva vana Botanical garden Bidar included angiosperms Pteridophytes and Gymnosperms. Abrus precatorius, Ephedra, Withania sominifera, Catharanthus roseus, Tinospora cardifolia, Andrographis paniculata, Phyllanthus amarus, allium sativum, Cocos nucifera, Coleus aromaticus, Curcuma longa, Martynia annua, Ocimum tenuiflorum, Tamarindus indica, Terminalia chebula,Tithonia diversifolia, Acalypha indica, Brassica juncea, Clitoria ternatea, Datura metal, Delonix elata, Euphorbia antiquorum, Luffa acutangula, Madhuca longifolia, Myristica fragrans, Santalum album and Vitex negundo are some of the important medicinal plants of Deva Deva vana Botanical garden Bidar district of karnataka.